Barriers to the Successful Mentoring of Faculty of Color. (October 2022) - Davis, Tangier M.; Jones, Martinque K.; Settles, Isis H.; Russell, Paulette Granberry
Mentoring is important for career success and has been suggested to promote the advancement of faculty of color (FOC). However, some mentoring experiences may be negative and impede faculty's success. Building upon social cognitive career theory (SCCT), the current study examines whether FOC perceive challenges around receiving mentoring and applies an intersectional lens to assess whether these challenges vary by race/ethnicity and gender. We interviewed 118 tenure-track FOC from a predominantly White, research-intensive institution. We found that FOC experienced four mentoring challenges: negative mentoring experiences, difficulty finding mentors, insufficient institutional support for formal mentoring, and lack of post-tenure mentorship among tenured faculty. We also found that Black and Latinx women were most likely to describe barriers to mentoring whereas Asian and Black men reported the fewest. We discuss the implications of our findings within the framework of SCCT, along with potential interventions that may increase positive mentoring experiences for FOC.